Pengaruh Media ICT Berbasis For VBA Excel Terhadap Self Confidence Matematis Siswa SD Pada Materi Bangun Ruang - Lysta Ambarwati Sholeha; Desi Novianti; Siti Chotimah (Departement of Mathematics Education, 2019)
The purpose of this study is to describe the confidence of MI students by using ICT-based media for VBA excel on space building material. The research method used is descriptive qualitative method. The research subjects were 23 students of MI Tazkya class VI. The instrument provided consisted of a student confidence scale questionnaire consisting of 25 definitions and 4 answer choices, namely 1. Strongly Agree (SS), 2. Agree (S), 3. Disagree (TS), 4. Very Disagree (STS ). The self-confidence questionnaire related to superior VBA-based ICT media consists of 5 indicators. The results of the study that showed the confidence of MI Tazkya students by using ICT-based media for superior VBA in the overall building material were classified as good and in accordance with 4 indicators that led to a good proposal for indicators Believe in support well, were they anxious (good), indicators and had drive for achievement (good); indicator Know your strengths and weaknesses (s good). There is one indicator that falls into the criteria, which is the indicator Feel free, and is responsible for its actions (enough). And it can be seen that on average all students are included in both criteria